Providing Efficient Driving Directions Using GPS and Driver’s Ability - Sivaiah, G; Krishna Rao, P (International Journal of Computer Sciences and Engineering, 2014)
The fastest services of path finding were provided by numerous web maps along with local search engines for a long instance. User behavior of driving typically differs in their progressing driving experiences hence a good quality routing service should believe three aspects such as routes, traffic, as well as drivers, which are far away from extent of shortest or fastest path computing. In our approach of finding driving directions, Variance Entropy Clustering method is used to find out allocation of travel time between two landmarks in dissimilar time period. Two stage routing algorithm used to find fastest and safest route to reach destination. Rough and refined are the two routing stage algorithm used. Label setting algorithm used to find shortest distance between source and destination. Interactive voting map matching algorithm used to construct Landmark graph. GPS equipped taxis are employed as mobile sensors searching traffic rhythm of a city in physical world. If instantaneous sensor data are obtainable for several road segments, our method is combined to make available improved routes for end users.